Physiological profiles of Saudi elite judo athletes - Alahmadi, M. A. (The International Scientific Journal of Physical Education and Sport Science, 2021)
One of the most highly physiologically demanding combat sports is judo, which requires an excellent level of physical fitness to be successful in international competitions. Although the physical and physiological characteristics of high-ranked judo athletes are well established, the characteristics of Saudi judo athletes have not been determined. Therefore, the aim of this study was to assess the physiological profiles of Saudi elite judo athletes. Fourteen judo athletes (mean ± standard deviation (SD) for age, 17 ± 4 years; body mass, 66.7 ± 21 kg; height, 160.2 ± 13.6 cm) performed a special judo fitness test (SJFT). Body fat percentage (BF%) was determined using the bioelectrical impedance scale. Handgrip strength was measured using a handgrip dynamometer, and flexibility was determined by using a sit-and-reach test. The mean ± SD of the index of the SJFT was 16.2 ± 1.6. The means ± SD of BF%, handgrip strength, and flexibility were 24.1 ± 7.2 (%), 31.4 ± 11.5 (kg), and 34.6 ± 6.7 (cm), respectively. We concluded that the SJFT performance and handgrip strength were lower, and BF% was higher in Saudi judo athletes compared to international elite judo athletes.